O abuso de direito na recuperação judicial - Crippa, Carla Smith de Vasconcellos (2013)
The subject of this academic work is the abuse of right in the judicial restructuring and its objective is to verify the criteria to allow the recognition and punishment of abusive behaviors in the judicial restructuring, analyzing the legal regulation of the abuse, its requirements and consequences. Law No. 11,101/2005 does not rule the abuse of right, being silent on this subject. However, we have seen abusive behaviors by creditors, debtors, shareholders and officers, violating the limits imposed by good faith, good manners and the economic and social purpose of the judicial restructuring. To avoid that such behaviors are not punished as a consequence of an omission in Law No. 11,101/2005, we investigate the regulation of the abuse by Brazilian Law and the possibility of application of such regulation to the judicial restructuring on a subsidiary basis. The investigation is primarily analytic, dealing with the conceptualization of judicial restructuring and abuse of right and the principles and laws applicable to them. It is also empiric, reviewing court precedents. This work aims at setting out parameters that may be used in the discussion of particular cases, as to contribute to the development of court precedents and to the drafting of fair and equitable judicial restructuring plans, which comply with the purposes of Law No. 11,101/2005